(untitled) (Bulletin of Kharkiv National University of Internal Affairs, 2020)
The role of legislation and state policy in minimizing the impact of threats to environmental safety in the field of automobile transport has been studied. The main directions of the development of state policy and legislation in the field of reducing the negative impact of motor vehicles on the environment and public health have been defined. The main problems of reducing the negative impact of motor vehicles on the environment and public health, as well as the development of state and legal mechanisms to overcome them have been determined. The main environmental problems faced by governments are the use of internal combustion engines and fuel quality indicators. Many EU countries are refusing to further impose more strict requirements on the operation of motor fuel engines, instead introducing mechanisms to completely abandon such vehicle propulsion systems. However, such a refusal raises another problem of greening of road transport – the problem of electrification of transport, in the process of which it is necessary to solve the problems of transport energy and disposal of used batteries of electric vehicles. The authors have emphasized on inexpediency that to be limited in the long run only to mechanisms for setting more strict emission requirements for cars. The authors have indicated the need for a comprehensive approach to solving environmental problems to prevent the emergence of new significant difficulties – the accumulation of used batteries of electric cars, the depletion of non-renewable resources for their manufacture, etc. It has been offered to join Ukraine to the pan-European initiative of electrification of road transport, to develop the state program for the transformation of the motor transport industry with clear deadlines for the introduction of restrictions on the use of internal combustion engines, to introduce mechanisms to financially stimulate the transition from internal combustion engines to electric combustion engines.